Antipsychotic, benzodiazepine and Z-drug prescriptions in a Swiss hospital network in the Choosing Wisely and COVID-19 eras: a longitudinal study (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: Physicians frequently prescribe antipsychotics off-label to treat, among others, insomnia and anxiety. The Swiss “smarter medicine – Choosing Wisely” campaign has tried to raise awareness about the risks and to limit benzodiazepine and Z-drug prescriptions. In the Italian-speaking part of Switzerland, our network of public hospitals joined the campaign with the aim of avoiding unnecessary benzodiazepine and Z-drug treatments, with prescription monitoring, benchmarking and educational contributions. Considering the risks of a possible shift towards the prescription of antipsychotics, and aware of the potential role of the COVID-19 pandemic, we decided to analyse the prescription trends of antipsychotics and benzodiazepines/Z-drugs before, during (2016–2017) and after the intervention.METHODS: For this longitudinal study, we reactivated a continuous monitoring of inpatient benzodiazepine/Z-drug and antipsychotics prescriptions/deprescriptions, paused in 2018 after the end of the internal Choosing Wisely campaign, based on routinely collected observational health data. We screened all demographic, administrative and prescription data of patients admitted to the internal medicine department of the four teaching hospitals (H1-H4) belonging to the EOC (Ente Ospedaliero Cantonale) network, from the fourth quarter of 2014 to the second quarter of 2023.RESULTS: We analysed 74,659 hospital stays (14,645 / 16,083 / 24,285 / 19,646 at hospitals H1 / H2 / H3 / H4 respectively). The mean (± SD) case mix (a metric that reflects the diversity, complexity and severity of the treated patients) and patient age were 1.08 ± 0.14 and 73 ± 2 years. 10.6% and 12.1% of patients received antipsychotics prior to admission and at discharge respectively (new prescriptions 3.3 ± 0.7%; deprescriptions 13.3 ± 5.2%). New prescriptions showed an upward trend, with +0.20% per year (p